Pediatric pituitary neuroendocrine tumors–a 13-year experience in a tertiary center - Li, Xiaoxu; Deng, Kan; Zhang, Yi; Feng, Ming; Xing, Bing; Lian, Wei; Yao, Yong (Frontiers in Oncology, 2023)
Introduction Pediatric pituitary neuroendocrine tumor is a rare condition, and despite previous research focusing on this specific group, the main factors influencing the surgical cure rate have not been identified. Methods We conducted a single-center retrospective study on pediatric pituitary neuroendocrine tumor patients who visited Peking Union Medical College Hospital between 2010 and 2023. We collected data on their clinical characteristics, imaging features, surgical outcomes, and follow-up information. Additionally, we used multiple-factor logistic regression to investigate the factors affecting the surgical cure rate of pediatric pituitary neuroendocrine tumor. Results 232 patients were diagnosed with pediatric pituitary neuroendocrine tumors, with a higher incidence in females. The most common type was ACTH-secreting adenoma (90/232), followed by prolactin-secreting adenoma (63/232), and growth hormone-secreting adenoma (41/232). The majority of pediatric adenomas were macroadenomas (139/232), and some tumors were associated with cystic changes or hemorrhage (58/232), while a few exhibited invasion of the cavernous sinus (33/232). The results of the multivariate analysis indicated that the different hormone secretion types, macroadenoma or the presence of cystic changes or hemorrhage were not significant risk factors for the cure rate after the first surgery. However, the invasion of the cavernous sinus was found to be an important factor influencing the postoperative cure rate. Most pediatric pituitary neuroendocrine tumors with cavernous sinus invasion were macroadenomas, and some displayed characteristics of refractory pituitary neuroendocrine tumors, with some patients experiencing irreversible complications after surgery. Conclusion Pediatric pituitary neuroendocrine tumors are complex, and the postoperative cure rate is particularly poor for tumors with cavernous sinus invasion. Although macroadenoma itself does not significantly impact the postoperative cure rate, it is still recommended to diagnose and treat early to avoid unnecessary surgery or surgical complications.